Implementation of Risk-Based Governance Audit in Strengthening Local Government Governance at the Banjarmasin City Inspectorate - Zulva, Indana; Kristanto, Budi (Program Pascasarjana Universitas Negeri Makassar, 2025)
This study aims to examine the implementation of a Risk-Based Governance Audit (GBA) at the Banjarmasin City Inspectorate and its contribution to strengthening local government governance. The research employed a descriptive qualitative method with a case study design, using in-depth interviews, participatory observation, and audit document analysis, analyzed through the interactive model of Miles & Huberman. The results show that the Banjarmasin Inspectorate has implemented a Risk-Based Annual Supervision Work Program (PKPT) by categorizing Regional Apparatus Organizations (OPD) based on vulnerability levels, indicating improvements in the Government Internal Control System (SPIP), Risk Management Index (MRI), and Corruption Control Effectiveness Index (IEPK). However, the limited number of certified auditors, weak local regulations, and bureaucratic cultural resistance remain significant challenges. This research expands the GBA model by incorporating the dimension of bureaucratic culture as a determinant of risk-based audit effectiveness while reinforcing the role of risk-based GBA in enhancing transparency, accountability, and the overall effectiveness of local government governance.